Ekstrak etanol daun pandan wangi (pandanus amaryllifolius r.) 10% menurunkan immobility time dan kadar kortisol tikus jantan galur wistar yang depresi - Lia Puspitasari (Intisari Sains Medis, 2017)
Depression is an emotional and soul disorders that occurs due to abnormality of serotonine, norepinephrine, dopamine and cortisol levels in blood, urine and cerebrospinal fluid. Herb that assumed have antidepresant activity and able to normalise this abnormality condition is pandan leaf (Pandanus amaryllifolius R) with some secondary metabolites. The purpose of this reseach is to investigate the effect of pandan leaf extract in decreasing immobility time and cortisol levels in male wistar induced depression.This research used experimental laboratory pretest and posttest control group design, with 24 sample that divided into four group. Depression was inducted with tail suspention test method for 3 minutes a day in 10 days. Antidepressant activity observed by measurement of immobility time in forced swimming test method and analysis of cortisol levels with ELISA method. Based on the results of this research, ethanol extract of pandan leaves 10% able decreased immobility time for 45,26% (p<0,05) and decreased cortisol level for 33,24% (p<0,05). In t-paired test analysis, extract ethanol of pandan leaves 10% showed that there was an influence with this treatment in immobility time and cortisol level pretest and posttest data (p<0,05). Another result from this research showed that ethanol extract of pandan leaves 10% did not decrease immobility time and cortisol levels more better than positive control (amitriptilin treatment) p<0,005. It can be concluded that administration of extract ethanol pandan leaves 10% decreased immobility time and cortisol levels in depression male wistar rats.Â Â